Genotype and expression analysis of two inbred mouse strains and two derived congenic strains suggest that most gene expression is trans regulated and sensitive to genetic background - Noyes, H.A.; Agaba, Morris; Anderson, S.; Archibald, A.L.; Brass, A.; Gibson, John P.; Hall, L.; Hulme, H.; Oh, S.J.; Kemp, Stephen J. (Springer, 2010)
Differences in gene expression may be caused by nearby DNA polymorphisms (cis regulation) or by interactions of gene control regions with polymorphic transcription factors (trans regulation). Trans acting loci are much harder to detect than cis acting loci and their effects are much more sensitive to genetic background.